IMPACT OF CADMIUM ON THE GROWTH AND DEVELOPMENT OF PINUS SYLVESTRIS - Valter, G.; Voronova, Ye.; Onats’ka, N.; Вальтер, Г. А.; Воронова, Є. М.; Онацька, Н. М.; Воронова, Е. М.; Онацкая, Н. М. (Харьковский национальный автомобильно-дорожный университет, 2014)
The results of laboratory experiments of the effect of cadmium salt solutions on the growth processes and peroxidise activity in seedings of Pinus Sylvestris are presented.
ВПЛИВ КАДМІЮ НА РІСТ І РОЗВИТОК PINUS SYLVESTRIS
ВЛИЯНИЕ КАДМИЯ НА РОСТ И РАЗВИТИЕ PINUS SYLVESTRIS
Keywords: cadmium salts; toxicity; sprouting energy; germination rate energy; peroxidise activity; солі кадмію; токсичність; енергія проростання; енергія сходження; активність пероксидази; соли кадмия; токсичность; энергия проростання; энергия всхожести; активность пероксидазы; 57.033